ΒIII-tubulin overexpression is linked to left-sided tumor localization and nuclear β-catenin expression in colorectal cancer. (2015) - Melling, Nathaniel; Tsaklakidis, Anastasia Martha; Simon, Ronald; Stahl, Philip; Bokemeyer, Carsten; Terracciano, Luigi; Sauter, Guido; Izbicki, Jakob Robert; Marx, Andreas Holger
Abstract: Introduction/Background: βIII-tubulin expression correlates with poor outcome in various malignancies. Materials and methods: βIII-tubulin expression was analyzed by immunohistochemistry on a tissue microarray containing 1800 colorectal cancers. Results were compared to clinic-pathological and molecular parameters. Results: βIII-tubulin expression was detectable in 79.2% of 1619 interpretable colorectal cancers. Whole tumor slide analysis showed that βIII-tubulin is homogenously expressed in CRC. High βIII-tubulin expression was associated with left-sided tumor localization ( p =0.0303) and nuclear β-catenin expression ( p =0.003). High βIII-tubulin expression was not linked to the gender of the patient ( p =0.5842). When all tumors were analyzed the prognostic role of βIII-tubulin expression was not independent of pT stage, pN stage, tumor grade or tumor localization ( p =0.0517). Conclusion: βIII-tubulin expression is not an independent prognostic parameter in colorectal cancer. The significant association with left-sided tumor localization and a key genomic alteration of colorectal cancer such as β-catenin suggest interaction with important pathways involved in colorectal cancer.